Role of Ectopic Gene Conversion in the Evolution of a Candida krusei Pleiotropic Drug Resistance Transporter Family - Lamping, Erwin (Genetics, 2017)
Gene duplications enable the evolution of novel gene function, but strong positive selection is required to preserve advantageous mutations in a population. This is because frequent ectopic gene conversions (EGCs) between highly similar, tandem-duplicated, sequences, can rapidly remove fate-determining mutations by replacing them with the neighboring parent gene sequences. Unfortunately, the high sequence similarities between tandem-duplicated genes severely hamper empirical studies of this important evolutionary process, because deciphering their correct sequences is challenging. In this study, we employed the eukaryotic model organism Saccharomyces cerevisiae to clone and functionally characterize all 30 alleles of an important pair of tandem-duplicated multidrug efflux pump genes, ABC1 and ABC11, from seven strains of the diploid pathogenic yeast Candida krusei. Discovery and functional characterization of their closest ancestor, C. krusei ABC12, helped elucidate the evolutionary history of the entire gene family. Our data support the proposal that the pleiotropic drug resistance (PDR) transporters Abc1p and Abc11p have evolved by concerted evolution for ∼134 MY. While >90% of their sequences remained identical, very strong purifying selection protected six short DNA patches encoding just 18 core amino acid (aa) differences in particular trans membrane span (TMS) regions causing two distinct efflux pump functions. A proline-kink change at the bottom of Abc11p TMS3 was possibly fate determining. Our data also enabled the first empirical estimates for key parameters of eukaryotic gene evolution, they provided rare examples of intron loss, and PDR transporter phylogeny confirmed that C. krusei belongs to a novel, yet unnamed, third major Saccharomycotina lineage.